MODELS OF THE ORGANIZATION OF THE JUDICIAL SYSTEM:: THE EXPERIENCE OF RUSSIA AND FOREIGN COUNTRIES - S. Sinenko, Vladimir; G. Кhasanova, Sul'eta; D. Khlebnikov , Aleksandr; L. Rasskazov, Vyacheslav; M. Vasekina, Elvira (Gênero & Direito, 2020)
This article provides an overview of the organization of the judiciary in various countries. Firstly, attention is drawn to the legislative framework on the basis of which the system of courts in a particular state is built. Secondly, the conclusion is drawn that there are three models of the organization of the judiciary: decen-tralized; moderately centralized; strongly centralized bathroom. Examples of states in which distinguished models of the organization of the judiciary operate are given. Particular attention is paid to the place of the Russian model in the classification of judicial systems according to the degree of centralization of the judiciary.